Traditional healing practices in Kiwai, Balakot: Insights from ethnobotanical research in Kaghan Valley, Pakistan - Asim, Iram; Yasmeen, Humaira; Khan, Hubza Ruatt; Junaid, Kashaf (Ethnobotany Research and Applications, 2024)
Background: Using plants for traditional medicinal purposes has consistently held a significant position and has become increasingly important. Due to the underdeveloped healthcare system in Pakistan, the region is particularly intrigued by ethnobotanical and ethnomedicinal investigations. The present study aims to investigate the floral diversity of therapeutic plants in a remote region of Pakistan with a focus on therapeutic plants. Methods: The research was conducted between March 2023 to April 2024 in Thubi Village of Kiwai, Kaghan Valley. Semi-structured interviews were used to gather data. Health Organization Family of International Classifications, approved by the World Health Organization Family of International Classifications, used to group therapeutic uses into 14 disease categories. The data was evaluated through ethnobotanical indices like Use Value (UV), Relative Frequency of Citation (RFC) and Consensus Index (CI %). Results: The study reported 69 plants from 39 different plant families. Out of 69, 40 plant species (57.9%) were herbaceous with Rosaceae being the most (9, 13%) prevalent species. Hedera helix L. has the highest use value of 0.92. For Solanum tuberosum L., the highest relative citation frequency was documented (0.94). The consensus index for Prunus armeniaca L. was the greatest (94%). The conservation status of species was detected according to the IUCN Red List showing 30 species (43.48%) were endangered, 23 (33.33%) were vulnerable, 10 (14.49%) were of least concern and 6 plant species (8.7%) were not threatened. Conclusions: Some unexpected uses of medicinal plants were revealed by the ethnobotanical study conducted in Kiwai Valley. Members of the local community and traditional healers participated in the survey. They contributed important data about medicinal plants that will aid in future studies and the development of new drugs. Keywords: Ethnobotany; Traditional knowledge, Conservation; ICPC, Consensus Index